Anatomization of the overall equipment effectiveness (OEE) for various machines in a tool and die shop. Issue 1 (25th March 2022) - Raju, Sagarika; Kamble, Harsha Arun; Srinivasaiah, Rashmi; Swamy, Devappa Renuka
Abstract : Purpose: The purpose of this research is to discover equipment losses and assess the accomplishment of overall equipment effectiveness (OEE) values. Design/methodology/approach: Industries specialized in die shops often have issues regarding their efficiencies, conferring to statistics further production line department procedure for various machines frequently suffered restrictions owing to excessive downtime and speed losses in machines thus, reducing their effectiveness and efficiency. OEE is a means of determining how effective a piece of equipment is when in working condition. Calculation of OEE finds the heart of the issue and the root cause for the underlying problem. Findings: The dimensional outcomes suggest that the average machine effectiveness has not attained the norm of >85%, but there is still room for progression. Originality/value: One recommended procedure to reduce losses is to keep the actual pace of operation and downtime of equipment constant. Many such suggestions are provided to reduce the losses.